2016
DOI: 10.3823/1885
|View full text |Cite
|
Sign up to set email alerts
|

Legionella native valve endocarditis case report and review of literature

Abstract: Background: Legionella native valve endocarditis is exceedingly rare, and to the best of our knowledge, this is the first case complicated by a septic spleen infarction.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 12 publications
0
1
0
Order By: Relevance
“…Legionella mostly causes pneumonia by direct inhalation of contaminated aerosol. Extrapulmonary manifestations of Legionella infections include myocarditis, pericarditis, and endocarditis [6][7][8]. Compain et al [9] reported in a case of chronic endocarditis caused by Legionella Anisa in the bioprosthetic aortic valve.…”
Section: Resultsmentioning
confidence: 99%
“…Legionella mostly causes pneumonia by direct inhalation of contaminated aerosol. Extrapulmonary manifestations of Legionella infections include myocarditis, pericarditis, and endocarditis [6][7][8]. Compain et al [9] reported in a case of chronic endocarditis caused by Legionella Anisa in the bioprosthetic aortic valve.…”
Section: Resultsmentioning
confidence: 99%
“…It was first discovered in 1984, and only 16 cases had been reported by 2016. Of these 16 patients, only two had healthy and normal heart valves, and the others had a history of valve surgery (26). PCR and culture-based methods are the gold standards for Legionella detection.…”
Section: Discussionmentioning
confidence: 99%